Evaluation and Changes in the Comprehensive Ecological Effects of Agriculture in Urbanizing Areas: A Case Study of the Xi'an Metropolitan Zone, China - Zhongxue Zhou; Fangze Zhao; Bingjie Song (Ecological Indicators)
Agricultural systems have significant negative impacts on the global environment. Current research across ecology, geography, and environmental science often suffers from overlapping or contradictory concepts, complicating comprehensive assessment. Moreover, there is insufficient analysis of the fundamental properties of agroecosystems, and a gap exists in the comprehensive analysis of the overall ecological effects of agricultural systems. This study redefines agricultural ecological functions from a multidisciplinary perspective and proposes a framework for assessing the comprehensive ecological effects of agriculture on local ecosystems. The framework integrates research on ecosystem services, biodiversity, carbon emissions, pollution, and ecological stability. Using the Xi’an metropolitan zone as a case study, this research evaluates the ecological utility of different agricultural types and examines changes during agricultural transformation. Key findings include: (1) The comprehensive ecological effects of agriculture decline when transitioning from grain planting to urban agriculture, as modern agricultural practices in urbanizing areas are ecologically detrimental compared with natural ecosystems. (2) The shift from grain to urban agriculture, excluding vegetables, generally enhances ecosystem services, complexity, and stability, due to changes in the natural properties of crop types (e.g., trees, vines, or herbs), plant density, biodiversity, and leaf area index. (3) The negative environmental impacts of urban agriculture primarily reduce the comprehensive ecological effects due to unsuitable agricultural practices. Improving these practices can alleviate the environmental burden in urbanizing area. (4) The proposed framework provides a comprehensive and scientifically valid approach for assessing agricultural ecological effects and identifying their sources, with broad applicability.